EVALUATION OF EFFICACY OF KILLED AND COMMERCIALLYAVAILABLE LIVE NEWCASTLE DISEASE VACCINE IN BROILER CHICKENS IN PAKISTAN - M. Alia; B. Muneera; Z. Hussaina; S. F. Rehmanib; Tahir Yaqubb; M. Naeemc (Journal of Animal and Plant Sciences, 2014)
The study evaluated the efficacy of Newcastle Disease killed and commercially available live vaccine. Moreover, study also highlighted the inappropriate use of Newcastle Disease live vaccine as a booster dose providing the space to virus for its growth and multiplication in semi controlled broiler farms creating threat to whole poultry industry. Serum antibodies level was assessed by Haemagglutination Inhibition method and efficacy of Newcastle Disease killed and live vaccine was also determined using challenge test. Group “A” immunized with killed vaccine using homologous strain provided 90% to 100% protection. However, group “B” immunized with Newcastle Disease live vaccine (Heterologous strain) provided protection not more than 60% when challenged with velogenic viscerotropic form of Newcastle Disease Virus isolated from the recent outbreak. The results of the present work concluded that oil emulsified killed vaccine provided good protection using indigenous isolate against Newcastle Disease. Regression analysis showed highly significant (P<0.001) correlation between antibodies titre against Newcastle Disease versus age of the flock in group immunized with killed vaccine and significant (P<0.01) correlation in that group immunized with live vaccine.
Keywords: Newcastle disease; killed vaccine; commercial live vaccine; broiler